Karl Marx and the Geographies of the Present - Aroch Fugellie Paulina (Open Cultural Studies, 2018)
The oversaturation of information that characterizes the “digital age” is not only a question of large numbers of competing discourses blurring meaning itself out, but also of a fundamental disassociation between words and their use, between the constative and the performative dimensions of language. Baudrillard has analysed how the mutability of signs in our society has rendered meaning meaningless, through an infinite game of simulacra and simulation that forecloses our understanding of reality rather than making it legible. Meanwhile, Sloterdijk and Žižek have approached the same problematic from a different angle, analysing how actions perform an ideological foreclosure that cannot be observed when analysing signs alone. What discourses say and what they actually do today is often contradictory and this contradiction fulfills an ideological function. This is especially troubling when discourses declare themselves to be counter-hegemonic yet actively participate in the reproduction of the status quo. In this context, it is pertinent to return to the work of Marx to reflect on and engage with his coherent articulation of words and their use, of words and actions, and of the intellectual and the political. The coherence of his discourse and praxis offers tools to think through, if not seek to transform, the alienated semiotic landscape of our times.